A novel plant-internal route of recycling sulfur from the flue gas desulfurization (FGD) ash through sintering process: From lab-scale principles to industrial practices. Issue 1 (February 2022) - Ma, Kaihui; Deng, Junyi; Ma, Panshuai; Sun, Chengfeng; Zhou, Qi; Xu, Jian
Abstract: An efficient and sustainable solution to environmental issues is the utilization of solid waste that is generated from industrial and residential activities, and recycling the valuable components. This work proposes a novel route for plant-internal recycling that utilizes the ash produced by the dry flue gas desulfurization (FGD) process. The transient reaction behaviors of sulfur in the FGD ash that undergoes sintering process, which is equipped with the activated carbon adsorptive FGD process and sulfuric acid production, are evaluated from lab-scale principles to industrial practices. First, an X-ray photoelectron spectroscopy-based (XPS) quantitative analysis method was established to distinguish calcium sulfite (CaSO3 ) from calcium sulfate (CaSO4 ), and the linear correlation determines that nearly 90 wt% of the sulfur in the FGD ash exists in CaSO3 . Second, the subsequent oxidation of CaSO3 to CaSO4 was completed by 1000 °C under simulated sintering conditions, and before being emitted as sulfur dioxide (SO2 ) gas, the sulfur accumulates near edges of various-shaped protrusions as CaSO4 recrystallizes above 1200 ℃. Third, the mass balance calculations based on the sintering pot experiments revealed that approximately 90 wt% of total sulfur was released in the exhaust flue gas, and the SO2 concentration abruptly increases when the sintering process is close to end. Finally, industrial practices proved that the current recycling of FGD ash accounted for 91% of the overall processing capacity of the proposed route, and approximately 98 wt% of sulfur in the flue gas was recycled for sulfuric acid production. Graphical Abstract: ga1 Highlights: A feasible technology for the recovery and treatment of solid waste is proposed. A proposed correlation quantifies CaSO3 and CaSO4 in desulfurized ash. The sulfur mass balance is established via sintering pot experiments. FGD ash accounts for 91% of the overall processing capacity of the proposed route. 98 wt% of the sulfur in the flue gas has been recycled in practical practices.